Konstelasi Budaya dalam Pembentukan Sistem Pendidikan: Studi Perbandingan Indonesia, Jepang, Finlandia, dan Singapura - Adi Asmara; Kashardi; Asmi Astuti; Dharmawati Ambarita; M. Thoha; Atik Maryanti (Kartika: Jurnal Studi Keislaman, 2025)
Culture plays an important role in shaping thinking patterns, values, and educational practices across countries. This article aims to analyze the influence of culture on Indonesia's education system and compare it with several other countries, such as Japan, Finland, and Singapore. Through a literature-based approach, the study identifies that cultural differences result in variations in teaching methods, teacher-student relationships, disciplinary approaches, and educational objectives. In Indonesia, a collectivist culture and respect for authority tend to emphasize structured, teacher centered learning. In contrast, Finland highlights an egalitarian culture that supports independence and student-centered learning. Japan exhibits a culture of hard work and high discipline, while Singapore emphasizes strong competitiveness in line with its work-oriented culture. The findings indicate that culture significantly contributes to the characteristics of a country's education system. Understanding these cultural influences is essential for designing relevant and contextual educational innovations in Indonesia.